Materials science and technology : a comprehensive treatment. Volume 17B, Processing of ceramics Part II / edited by R.W. Cahn, P. Haasen, E.J. Kramer; Vol. editor : Richard J. Brook - Brook, Richard J.
Vol. 17B Processing of ceramics Part II in 1996